Strategi Public Relations Kementerian Pariwisata dan Ekonomi Kreatif dalam Membangun Media Relations - Elpa Hermawan (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
The aims of study were to obtain in-depth information about public relations (PR) strategies from the Ministry of Tourism and Creative Economy in implementing media relations. Media relations is the main key in public relations to convey and control information to the public. Public relations require the media in achieving its goals. The research method was qualitative descriptive. Data is taken from the Ministry of Tourism and Creative Economy document. Data analysis consists of data reduction, data presentation, and drawing conclusions. The results of the study concluded that the Ministry of Tourism and Creative Economy has two media strategies namely the first POP (pre event, on event, post event). This strategy is carried out through a variety of interesting activities. Second is POSE (paid media, owned media, social media, endorsers). This strategy is quite effective in conveying information to the public about Indonesian tourism. From the implementation of the media, the Ministry of Tourism and Creative Economy received various awards. This also has an impact on increasing the interest of tourists to Indonesia both from domestic and abroad.